Observations about the mucuna - corn system in the slopes of Waslala, Atlantic Region of Nicaragua. - Philipp, Dirk; Gamboa, William (Agronomía Mesoamericana, 2003)
A velvet bean-corn system utilized in hillside farming in Waslala, Nicaragua, was described and analyzed regarding farmer.s approaches to conservational practices in agriculture. Data suggested that the fresh biomass yield for velvet bean ranged from 11.4 to 60 t/ha, while the corn yield varied from 1.1 to 5.4 t/ha. Apparently, the economic efficiency of the velvet bean-corn system depended on the origin of the velvet bean seeds and at what level additional labor was employed. Data indicated that farmers who used own velvet bean seeds increased their gross income by $185.80/ha. Additionally, when only family labor was employed, the gross income increased by $265.11/ha compared to farmers who utilized hired labor and obtained bean seeds off-farm. Suggestions on how the described system may be improved regarding its sustainability are included by the authors.